IMPACT OF SPORT-PERFECTIONISM AND SELF-EFFICACY ON ACHIEVEMENT MOTIVATION AND SPORTS PERFORMANCE (A CASE STUDY OF INDIVIDUAL DIFFERENCES OF UNIVERSITY STUDENTS OF DISTRICT LAHORE) - Naveed Ahmad; Dr. Mohibullah Khan Marwat; Dr. Yasmeen Iqbal; Dr. Rahila Nizami; Muhammad Shah; Samera Saman; Kashif Mehmood (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Background: A wide range of literature focuses on the interaction of individual differences (I.D.) and success in life. Many I.D. are expected to bring success or failure in an individual's life. Part of I.D. Objective(s): This study was conducted with four different objectives including to explore the relationship between types of perfectionism and achievement motivation of university level male players; to explore the relationship between level of sports-self-efficacy and achievement motivation of university level male players; to examine the impact of perfectionism and sports-self-efficacy on achievement motivation and sports performance of university level male players and to identify individual differences in perfectionism sports-self-efficacy and achievement motivation. Methodology: This study employed cross-sectional research design, in which university level male players of 18-25 years of age participated. All the variables for this study were measured by using Multidimensional Perfectionism Scale, Sports-Self Efficacy Scale, and Achievement Motivation Scale. Other than the descriptive analysis, Regression Analysis was also done for hypothesis testing. Results: The findings indicated that perfectionism and sports self-efficacy had positive impact on achievement motivation and sports performance. Conclusion: The current research found that perfectionistic players reported having the highest levels of self-efficacy than the levels of self-efficacy of non-perfectionistic players.